Evaluation of infertility in women from an industrial area in Telangana, India by diagnostic hysterolaparoscopy: can it explain the unexplained? - Kanungo, Leena; Haritha, Mylavarapu; Chaitanya, Nerakh; Sangeetha, Katroth (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Infertility with a prevalence of 10-15% worldwide has been showing a rising trend. Diagnostic hysterolaparoscopy (DHL) procedure in infertility cases uncovers conditions which even a detailed clinical examination or hysterosalpingography or transvaginal ultrasound can miss. Correction of these factors improves chances of conception, naturally or by subsequent ART procedures. Methods: This is a prospective study conducted from January 2014 to December 2015. The objective of this study is to evaluate the factors causing infertility by diagnostic hystertolaparoscopy among primary and secondary infertility women coming from an industrial area, attending infertility clinic at Employees State Insurance Corporation Hospital, Telangana. 80 cases of primary infertility (65%)and secondary infertility (35%) belonging to age group of 19 to 35 years and above, satisfying the inclusion criteria underwent a systematic way of evaluation by diagnostic hysteroscopy followed by diagnostic laparoscopy procedure. Results: 40.38% of primary infertility and 35.72% of secondary infertility had abnormal pelvic pathology. 27% of primary and 32.14% of secondary infertility had abnormal intrauterine abnormality. Diagnostic hysteroscopy found intrauterine septum and endometrial polyp in 12.5% and tubal ostial fibrosis in 5% of total cases. Pelvic peritoneal adhesion (23.75%), pelvic endometriosis (13.75%) and tubal pathology (18.75%) were most common laparoscopic findings. 32.5% of all cases had no significant abnormality. Bilateral tubal block was seen in 20% of cases on chromopertubation. DHL also facilitated operative interventions like adhesionolysis, endometriotic tissue ablation, ovarian cyst drilling, septal resection, polypectomy in the same sitting. Conclusions: DHL procedure has become the gold standard diagnostic modality, as it explains 30-70% of factors that remained undetected during routine investigative workup of female infertility, especially those grouped under unexplained infertility. Industrial toxin exposure may lead to infertility as this study among industrial workers showed a greater incidence of tubo-peritoneal pathology than other factors.